Digital Drugs and the Culture of Cyber Addiction - qasim mohammed, Assist. Lect. Baneen; hussien jehad , Researcher. Yousif (Basra studies journal, 2025)
Contemporary societies face new challenges in mental and behavioral health due to rapid developments in digital communication technologies. Among the most prominent emerging phenomena are so-called "digital drugs" or "binary taps." These consist of audio frequencies broadcast through headphones and are believed to produce psychological or neurological effects akin to traditional drugs. These digital substances are often used online, and some users report experiencing euphoria, relaxation, or detachment from reality. This has raised concerns regarding their relationship with "cyber addiction" or "digital addiction," indicating a state of psychological and behavioral dependence on technological media. This study analyzes the relationship between digital drug use and the culture of cyber addiction by examining its psychological and neurological foundations, social contexts, and legal and health implications. It also discusses the lack of societal and educational awareness regarding the dangers of these practices and the absence of explicit legislation criminalizing their use or monitoring their spread, particularly among adolescents and young adults.